Application of higher order spectral method for deterministic wave forecast - Clauss, Günther F.; Klein, Marco; Dudek, Matthias; Onorato, Miguel (Volume 8B: Ocean Engineering, 2014)
This paper addresses the Higher Order Spectral (HOS) method as very fast and accurate non-linear method for deterministic wave forecast. The focus of the paper lies on wave propagation, with the objective to draw conclusions on the applicability of the HOS method for deterministic wave forecast. Systematic numerical and experimental investigations are conducted. The investigations comprise exact solutions of the nonlinear Schrödinger equation (NLS) as special non-linear wave groups, which are used as initial conditions for the subsequent simulations. Different parameters such as relative water depth, wave steepness and propagation distance are varied to evaluate the applicability of the HOS method. The results obtained are validated by experiments as well as fully non-linear simulations. It is shown that the HOS method is capable for non-linear wave forecast due to high accuracy and fast calculation time at once.